Cover Image, Volume 170A, Number 7, July 2016. Issue 7 (17th June 2016) - Giorgio, Elisa; Ciolfi, Andrea; Biamino, Elisa; Caputo, Viviana; Di Gregorio, Eleonora; Belligni, Elga Fabia; Calcia, Alessandro; Gaidolfi, Elena; Bruselles, Alessandro; Mancini, Cecilia; Cavalieri, Simona; Molinatto, Cristina; et al.
Abstract : The cover image, by Alfredo Brusco et al., is based on the Original Article Whole exome sequencing is necessary to clarify ID/DD cases with de novo copy number variants of uncertain signifi cance: Two proof‐of‐concept examples, DOI:10.1002/ajmg.a.37649 .